Accurately Assessing Teacher ADHD-Specific Attitudes Using the Scale for ADHD-Specific Attitudes. Issue 5 (March 2023) - Mulholland, Sarah; Cumming, Therese M.; Lee, Jihyun
Objective: The aim of this study is therefore twofold, first to accurately examine the ADHD-specific attitudes of New South Wales Government school in-service teachers using the Scale for ADHD-Specific Attitudes (Authors 2016), and second, to determine if any of their socio-demographic features could predict their attitudes Method: Exploratory factor analysis found a 5-factor structure, and multiple regression analysis was performed to establish the existence of groups of variables with respect to teacher attitudes towards ADHD-type behaviours and any demographic predictors of teacher attitudes. Results: The final regression model found significant predictors of each factor with R2 values ranging from .007 to .147. Conclusion: This study illustrated that teachers had generally positive attitudes towards students who display ADHD-type behaviours, however, they found the externalised behaviours of ADHD irritating in the classroom and found teaching students with ADHD-type behaviours difficult, and teachers want more information about ADHD and how to manage it in the classroom.